Immunohistochemical differential expression of p16 proteins in follicular type and plexiform type ameloblastoma - Haris Budi Widodo; Anung Saptiwulan; Helmi Hirawan; Christiana Cahyani Prihastuti; Tirta Wardana (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Differences in histopathological features that describe the growth mechanism and biological behaviour of follicular and plexiform ameloblastomas are associated with benign, aggressive and destructive tumour markers. p16 has inhibitory interactions between cyclin D and CDK 4/6 to block the cell cycle and alterations related to severity. Purpose: This study intends to evaluate and determine differential expressions of p16 protein in follicular and plexiform ameloblastomas. Methods: This is a descriptive analytics study. A total of 21 specimens consisting of follicular and plexiform ameloblastomas and healthy gingiva tissues as the negative control were examined using the immunohistochemistry assay. The analysis of p16 protein expression was interpreted by immunoreactive scoring. Statistical analysis was conducted using SPSS software with the Mann–Whitney test. A p-value <0.05 shows the significance of the change in expression. Results: An increased expression of p16 protein was found in the follicular ameloblastoma type (2.13 ± 1.808) and the plexiform type (4.44 ± 2.506) in comparison to the negative control group (0 ± 0). The increase of p16 expression in the follicular and plexiform ameloblastomas was significant compared to the negative control group (p-value <0.05); however, there was no significant difference between either type of ameloblastoma (p-value >0.05). Conclusion: The highest intensity of p16 protein expression was found in the plexiform type, even though it was not significantly different from the follicular type ameloblastoma.